Advancements in concussion prevention, diagnosis, and treatment - Bonds, G. B.; Edwards, W. W.; Spradley, B. D. (The Sport Journal, 2014)
Concussions continue to be a mainstay topic of conversation among the media, health professionals, and the general public. In 2013, the American Medical Society for Sports Medicine (AMSSM) released a position statement that estimated as many as 3.8 million concussions occur within sports annually with up to 50% of concussion injuries unreported. Advancements in the areas of diagnosis, treatment, playing rules, equipment, education, and technology have heightened the awareness on the dangers of concussion injuries and the need to provide better protection for sports participants. The current (2014) position statement from the National Athletic Trainers Association recommends a thorough neurologic assessment for a "history of concussion, seizure disorder, cervical spine stenosis, or spinal cord injury". In 2014, prominent organizations such as the National Collegiate Athletic Association (NCAA) and the National Football League (NFL) have taken a proactive approach to commission research projects to study the short term and long-term effects of concussion injuries. Results of these research efforts should enhance the welfare and protection of participants. The purpose of this paper is to review and explore advancements in concussion prevention, diagnosis, treatment, playing rules, equipment, education, and technology.